ANALYSIS OF THE EFFECT OF PARTICIPATIVE BUDGET ON BUDGET GAP IN APBD ASAHAN DISTRICT WITH ASIMETRY INFORMATION, ORGANIZATIONAL COMMITMENT, ORGANIZATIONAL CULTURE, AND INDIVIDUAL CAPACITY AS MODERATION VARIABLES - satria, supkhi ridho (Asosiasi Dosen Akuntansi Indonesia, 2018)
The purpose of this study was to analyze and determine the effect of participative bugeting to budgetary slack with moderation variables, information asymmetry, organizational commitment, organizational culture and individual capacity through research of causality type. The population in this study are Civil Servants (PNS) who work in the Government of Asahan District who have middle and lower positions (Echelon III and IV). The sample of respondents was chosen with non probability sampling and determination of amount of samples with Slovin formula obtained 230 respondents. Data were collected by survey method through questionnaire and analyzed by t test and interaction test (moderation regression analysis). The results showed that participative bugeting had a significant and positive effect on the budgetary slack. Information asymmetry and organizational culture strengthen, while organizational commitment weakens the relationship between participative bugeting and budgetary slack. Individual capacity is unable to moderate the relationship between participative bugeting and budgetary slack.